Gender, Power, and Military Occupations: Asia Pacific and the Middle East since 1945 - Matos, Christine de; Ward, Rowena (Routledge Research in Gender and History, 2012)
Military occupations and interventions have a gendered impact on both those engaged in occupying, and those whose lands have been occupied. Yet little is known about this gendered impact, in terms of both masculinities and femininities, either historically or in contemporary times. While research in this area has begun to grow since events in Iraq and Afghanistan, this collection helps redress the relative neglect by examining and analysing the impact of occupation on men and women, both occupied and occupier, in a variety of geographical spaces from Japan to Palestine to Iraq. Gendered perspectives are also intimately tied to analyses of 'power': how power is enacted by the occupier; how powerlessness is experienced by the occupied; how power is negotiated, shared, compromised, subverted, reclaimed; power as visible and invisible; institutional power; contested power in post-conflict societies; and power as discursively constructed. The term 'military occupation' is interpreted broadly to include occupation, interventions, the presence of military bases and peacekeeping/post-conflict operations. This interpretation allows space to demonstrate that the lines between each definition are blurred, especially when it comes to analysing gender and power.